Interconnection algorithm of a wide range of pervasive devices for the Internet of things - Tao Chi; Ming Chen (International Journal of Distributed Sensor Networks)
With the rapid development of wireless communications for network of things, more and more models for such networks-on-chip architectures have been created and used in a wide range of applications. In this article, the behaviors of wireless communications for such networks-on-chip architectures are analyzed at two layers. The physical layer behaviors consist of what frequency is used, how and when signals are transmitted, and how transceivers’ responses are decoded. The medium access control layer behavior consists of how to provide a reliable link between two peer medium access control entities. For the optimization objective of each layer, the specific problems surrounding the design of combined radio frequency identification/Bluetooth/Wi-Fi chips are considered at their respective layer, and then, corresponding optimization methods are carried out. The problem of optimization is defined as a linear programming problem in which each active transceiver is assigned to a channel on condition that all the constraint is met on every link. Each optimization procedure proposed in this article is performed through the adaptation of its objective, from each one of these layers, in order to minimize interference previously specified. In principle, the optimization can be made layer by layer separately. The optimization criteria consist of a specification of the behaviors of wireless communications (radio frequency identification, Bluetooth, Wi-Fi) and a set of constraints and goals. Our approach is to perform it independently within the given task, where the given task can be achieved with its sequencing graph entities, including automate selection, binding, and scheduling. We have implemented our algorithms on a field-programmable gate array and applied them to some off-the-shelf products. This methodology looks promising, not only for the results presented and obtained through computer simulations but also for its generality concerning to the kind of wireless network system used. Therefore, such methodology is expandable either to multi-core networks-on-chip architecture or also to the off-the-shelf products.